EVALUATION OF THE EFFECTIVENESS OF COMPLEX TREATMENT OF PATIENTS WITH CHRONIC ULCERS ON THE BACKGROUND OF DIABETES MELLITUS: THE ROLE OF IMMUNOMODULATORS IN THE HEALING PROCESS - Baxtiyorjon Y. Umarov (Central Asian Journal of Medicine, 2025)
The aim of this study is to evaluate the effectiveness of the use of immunomodulators in the complex treatment of patients with chronic ulcers on the background of diabetes mellitus. The study involved 100 patients divided into the main and control groups, in which different treatment methods were used. Immunomodulators were used in the main group, and standard therapy was used in the control group. Clinical outcomes were evaluated, including ulcer healing time, infection rate, antibiotic therapy, and complication rate. The average wound healing time in the main group was 35.6 ± 5.2 days, in the control group-48.9 ± 7.3 days. In the main group, the rate of wound infection was 47% (23 patients), in the control group — 65% (32 patients). The incidence of complications in the main group was 10% (5 patients), in the control group — 18% (9 patients). The use of antibacterial therapy in the main group was 70%, in the control group — 85%. The results of the study confirm that the use of immunomodulators promotes accelerated wound healing, reduces the frequency of infection and complications, which makes them an effective supplement in the treatment of chronic ulcers in diabetes mellitus.